POTENSI ANTIBAKTERI PAREM KARO UNTUK MENANGANI INFEKSI Staphylococcocus aureus PADA PENDERITA DIABETIC FOOT - Br Tarigan, Jenny Alfa Dilla; Sembiring, Novitaria Br; Bangar S, Roy Idrianto (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
One of the cronic and serious complications of diabetes mellitus is diabetic foot. Staphyloccocus aureus bacteria is the most common bacteria found in this type of wound. The purpose of this study is to determine the antibacterial activity of parem Karo, which is one of the traditional medicines of the ethnic culture of the Karo tribe which is rich in spices. Testing the antibacterial activity of Karo hot parem against staphylococcus aureus bacteria using disc diffusion method with 255, 50% and 75% concentration of Karo hot parem extract, positive control Ciprofloxacin Disks (5µg) and negative control DMSO 10%. This disc diffusion method was carried out to determine the diameter of the inhibition formed by Karo hot parem extract in inhibiting the growth of Staphyloccocus aureus bacteria. The results showed inhibitory activity at higher concentrations with the largest average inhibition diameter at 75% concentration against Staphyloccocus aureus bacteria (8.23 ± 0.72 mm) followed by 50% concentration with an average inhibition zone at all. The conclusion obtained from this study is that there is antibacterial activity of Karo hot parem extract at a concentration of 75% and 50% against the growth of Staphyloccocus aureus bacteria.